Pengaruh Pengumuman Perubahan Bond Rating Terhadap Return Saham Perusahaan di Bursa Efek Jakarta (Penelitian Periode 2003 s.d 2005) - Etikah Karyani; Adler H. Manurung (The Indonesian Journal of Accounting Research, 2013)
This study identifies the effect of corporate bond rating changes on common stock return. Data used is daily stock returns listed at JSX and the announcement of bond rating changes issued by PT PEFINDO and PT Kasnic Credit Rating Indonesia for the period of 2003-2005. To evaluate the market reaction of bond rating upgrade and downgrade, this study used cumulative average abnormal return. The abnormal return was measured using the event study methodology. The test result shows that the announcement of bond rating upgrade and downgrade does not carry the content of information for investors so that market does not significantly react on stock return. To investigate possible information of bond rating changes for three years, cross section regression is used. From the outcome of research shows that the increase of stock return is affected significantly by the increase of Earning per Share and the type of financial company that experienced upgrade of bond rating. This study also proves that the type of financial company affects stock return significantly for all changes of bond rating.